Evaluation of PBN spin-trapped radicals as early markers of lipid oxidation in mayonnaise. (1st January 2021) - Merkx, Donny W.H.; Plankensteiner, Lorenz; Yu, Yafei; Wierenga, Peter A.; Hennebelle, Marie; Van Duynhoven, John P.M.
Highlights: PBN impacts downstream lipid oxidation reactions, limiting its use in mechanistical studies. In bulk oil and mayonnaise, the PBN-OOL adducts degrade to MNP, benzaldehyde and LO. With ESR, the primary molecule that is measured are the MNP-L adducts. ESR and 1 H NMR can assess antioxidant efficacy in the early stages of lipid oxidation. Abstract: Quality deterioration of mayonnaise is caused by lipid oxidation, mediated by radical reactions. Assessment of radicals would enable early lipid oxidation assessment and generate mechanistic insights. To monitor short-lived lipid-radicals, N - tert -butyl-α-phenylnitrone (PBN), a spin-trap, is commonly used. In this study, the fate of PBN-adducts and their impact on lipid oxidation mechanisms in mayonnaise were investigated. The main signals detected by Electron Spin Resonance (ESR) were attributed to L-radicals attached to 2-methyl-2-nitrosopropane (MNP), one of three degradation products of the PBN-peroxy-adduct. The second degradation product, benzaldehyde, was detected with Nuclear Magnetic Resonance ( 1 H NMR), in line with MNP-L adduct generation. For the third class of degradation products, LO-radicals, their scission products were detected with 1 H NMR and indicated that LO-radicals have a major impact on downstream oxidation pathways. This precludes mechanistical studies in presence of PBN. Degradation products of PBN-adducts can, however, be used for early assessment of antioxidants efficacy in oil-in-water emulsions.